2018
DOI: 10.21511/imfi.15(3).2018.03
|View full text |Cite
|
Sign up to set email alerts
|

Financial sector and manufacturing sector performance: evidence from Nigeria

Abstract: Nigerian economy depends on oil as the major source of revenue, failure to diversify the revenue base has raised questions about its sustainability and implication on the economy. This study uses market capitalization, broad money stock, credit to private sector, prime interest rate and deposit liability as proxies for the financial sector, while output in the manufacturing sector and manufacturing employment are used as proxies for manufacturing performance. The study examines the causal effects, shock effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 38 publications
0
30
1
Order By: Relevance
“…The LSDV estimate, however, shows that the reduction is to a significant degree. Considering the disparity in the estimates of the two techniques in the area of statistical significance, it may be safely concluded that increases in board size shrinks dividend 3 The fact that the firm size is also dependent on some factors, which may be used to increase its value, this variable may exhibit an endogenous nature. Yet, as stated under the estimation strategy, the inclusion of the time and entity/firm fixed effects are counted on to mitigate the possibilities of reverse causations.…”
Section: Resultsmentioning
confidence: 99%
“…The LSDV estimate, however, shows that the reduction is to a significant degree. Considering the disparity in the estimates of the two techniques in the area of statistical significance, it may be safely concluded that increases in board size shrinks dividend 3 The fact that the firm size is also dependent on some factors, which may be used to increase its value, this variable may exhibit an endogenous nature. Yet, as stated under the estimation strategy, the inclusion of the time and entity/firm fixed effects are counted on to mitigate the possibilities of reverse causations.…”
Section: Resultsmentioning
confidence: 99%
“…Operational efficiency in the manufacturing sector continues to be a prominent issue among academics and industry players. An efficient manufacturing sector is an important solution to resolving the problems of unemployment and sustainable economic growth (Asaleye et al, 2018). The Rent Theory of Profit is one of the few theories that explain the impact of efficiency on profits (Bloom et al, 2018;Teece, 2017;Syversson, 2011;Walker, 1887).…”
Section: Literature Reviewmentioning
confidence: 99%
“…To address this, the Nigerian government seeks to place more emphasis on the development of the manufacturing sector in order to promote sustainable growth and development. It is believed that an improved manufacturing sector is a prerequisite for economic development (Asaleye et al, 2018). The sectors" contribution to GDP has not changed substantially over the course of the decade.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, informed the niche of this study. Likewise, most African countries are regarded as low-income countries when high unemployment rate and poverty are the major macroeconomic problems [29][30][31]. Hence, Sphenostylis stenocarpa can help to improve the nutritional quality of these resource-poor countries.…”
Section: Introductionmentioning
confidence: 99%